2015
DOI: 10.1177/0098628315603182
|View full text |Cite
|
Sign up to set email alerts
|

Psychology Students’ Understanding of the Skill-Based Learning Fostered Through University Assignments

Abstract: We examined first-year psychology majors' (N ¼ 195) beliefs about the relevance of two types of university assignments (individual essay and group wiki) and their connection to the development of career-related skills. Students reported that assignments were only somewhat relevant to their career goals, and relevance ratings were typically justified by referring to assignment features (content and type) rather than skill development. Our results suggest that it is important for faculty to be explicit with stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…It is possible that students find it easier to see the relevance of co-curricular activities to the "real world" in which they will have to live and work, and consequently believe that such experiences are more meaningful. Indeed, past research has suggested that students evaluate course-based assignments as being only moderately relevant, and this finding may reflect the fact that they often do not spontaneously recognize how those assignments foster skills that are transferable to their personal and professional lives (Martini, Rail, & Norton, 2015). Universities should develop ways to increase the actual and perceived relevance of course work.…”
Section: Student Perceptions Of Significant Learning Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that students find it easier to see the relevance of co-curricular activities to the "real world" in which they will have to live and work, and consequently believe that such experiences are more meaningful. Indeed, past research has suggested that students evaluate course-based assignments as being only moderately relevant, and this finding may reflect the fact that they often do not spontaneously recognize how those assignments foster skills that are transferable to their personal and professional lives (Martini, Rail, & Norton, 2015). Universities should develop ways to increase the actual and perceived relevance of course work.…”
Section: Student Perceptions Of Significant Learning Experiencesmentioning
confidence: 99%
“…Universities should develop ways to increase the actual and perceived relevance of course work. Suggestions include having faculty explicitly state the career-related skills that their course-based work is intended to foster and to emphasize the skills that are in demand by employers (Martini et al, 2015). Other strategies include increasing the relatedness felt by students; that is, increasing their sense of "what does this have to do with me?"…”
Section: Student Perceptions Of Significant Learning Experiencesmentioning
confidence: 99%
“…In fact, the returns that students report achieving from their degree appear to be constrained by their prior expectations of these gains. Second, students often appear to lack the language and awareness that are needed to talk about the benefits of their degree, particularly those associated with career-related skill development (Martini, Rail, & Norton, 2015). It would be useful to know if this is indeed the case, as it would suggest that more needs to be done to help students to articulate the full range of advantages associated with their degree.…”
Section: The Present Studymentioning
confidence: 99%
“…If this is the case, then it may be important for instructors to make the career-related transferable skills explicit in the activities and assignments put forward in their courses. This may be particularly important given past research suggesting that students aren't always aware of the skills developed through coursework, or how those skills might transfer to the work environment (Martini et al, 2015).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…It is possible that students find it easier to see the relevance of co-curricular activities to the "real world" in which they will have to live and work, and consequently believe that such experiences are more meaningful. Indeed, past research has suggested that students evaluate course-based assignments as being only moderately relevant, and this finding may reflect the fact that they often do not spontaneously recognize how those assignments foster skills that are transferable to their personal and professional lives (Martini, Rail, & Norton, 2015).…”
Section: Importance Of Co-curricular Experiences and Feelings Of Prepmentioning
confidence: 99%